1997
DOI: 10.1152/ajpcell.1997.273.4.c1371
|View full text |Cite
|
Sign up to set email alerts
|

β-Adrenergic regulation of constitutive nitric oxide synthase in cardiac myocytes

Abstract: Nitric oxide (NO) has been implicated in endogenous control of myocardial contractility. However, NO release has not yet been demonstrated in cardiac myocytes. Accordingly, endogenous NO production was measured with a porphyrinic microsensor positioned on the surface of individual neonatal or adult rat ventricular myocytes ( n > 6 neonatal and adult cells per experiment). In beating neonatal myocytes, there was no detectable spontaneous NO release with each contraction. However, norepinephrine (NE; 0.25–1 μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
72
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(78 citation statements)
references
References 25 publications
5
72
1
Order By: Relevance
“…In our previous publication, FeTPPS (10 μmol/L) alone was shown to have no effect on the cardiomyocyte response to ISO [13]. Additionally, studies have shown that acute β-adrenergic stimulation could alter endogenous nitric oxide production [24,25]. This change in nitric oxide levels could shift the equilibrium of nitric oxide and superoxide produced by SIN-1, potentially changing the level of peroxynitrite production.…”
Section: Low Sin-1 (10 μMol/l) and Myocyte Contractilitymentioning
confidence: 96%
See 1 more Smart Citation
“…In our previous publication, FeTPPS (10 μmol/L) alone was shown to have no effect on the cardiomyocyte response to ISO [13]. Additionally, studies have shown that acute β-adrenergic stimulation could alter endogenous nitric oxide production [24,25]. This change in nitric oxide levels could shift the equilibrium of nitric oxide and superoxide produced by SIN-1, potentially changing the level of peroxynitrite production.…”
Section: Low Sin-1 (10 μMol/l) and Myocyte Contractilitymentioning
confidence: 96%
“…However, upon repetition of the above experimental protocol with the addition of 10 μmol/L FeTPPS, the positive effect of 10 μmol/L SIN-1 on submaximal β-adrenergic stimulation was no longer observed (data not shown). Additionally, since endogenous nitric oxide production has been shown to change during acute β-adrenergic stimulation [24,25], we chose to inhibit endogenous nitric oxide production in another series of functional experiments using the L-arginine analog L-NAME, a non-specific inhibitor of nitric oxide synthase. After reaching steady-state in normal Tyrode control solution and a steady-state response to 0.01 μmol/L ISO, superfusion with 0.01 μmol/ L ISO+10 μmol/L SIN-1 in the presence of 100 μmol/L L-NAME still resulted in a significant increase in myocyte [ Fig.…”
Section: Effect Of Low Sin-1 (10 μMol/l) On Wt Myocyte Functionmentioning
confidence: 99%
“…12,4 Constitutive NOS (cNOS) and inducible NOS (iNOS) are both present in ventricular myocytes. 13,14 To examine if NO is involved in the action of leptin in starch and sucrose myocytes, the effect of leptin on PS was reexamined in the presence of the NOS inhibitor L-NAME (100 mM). L-NAME alone had no effect on PS over 30 min (data not shown).…”
Section: Experimental Animals and Plasma Leptin Levelmentioning
confidence: 99%
“…20 Constitutive NOS and inducible NOS are both present in cardiac myocytes. 21,22 To examine the potential mechanism of action for leptin, the effect of leptin on PS and intracellular Ca 2ϩ transients was reexamined in the presence of the NOS inhibitor L-NAME (100 mol/L). L-NAME alone had no effect on PS and intracellular Ca 2ϩ transients over 30 minutes (data not shown).…”
Section: Transients In the Presence Of L-namementioning
confidence: 99%